Dirar ibn Amr’s Understanding of Hadith in His Kitab al-Tahrish - Abdulhameed Majeed Ismael Al Sheesh (Darulfunun Ilahiyat)
Dirar ibn Amr’s book Kitab al-Tahrish is the oldest resource regarding the religious groups or factions. The book contains sources from the 2nd century AH and includes many hadith narrations these groups used as evidence to support their opinions against their opponents. In his book Ḍirar lists a given controversy and then provides the ḥadith of each factioncites to support their position regardless as it sound or fabricated. But what approach did the author of the book use when including these narrations? How accurately did he transmit the narrations in his book? Is there a similarity between the author’s uses of hadith and modernists’ understanding of hadith? This research seeks to answer these and other questions that are necessary to reveal the approach of the book and its author. After probing and classifying these texts, the book clearly is not including the same category of hadith in terms of accuracy. It contains sound, weak (i.e., incomplete sanad or with transmitters of questionable authority), and even fabricated narrations, some of which are not found in other sources. In addition, the author’s approach when referring to these narrations is considered inaccurate compared to the methods of modern sources and sometimes contains words that have been distorted from what is factual.